PENANGANAN PELANGGARAN TINDAK PIDANA PEMILU OLEH BADAN PENGAWAS PEMILU DI KABUPATEN BANDUNG (Perkara Keterlibatan Kepala Desa Majasetra pada Pemilu tahun 2024) - Kahpiana; Diding Rahmat (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2025)
The issue of impartiality among village government officials in elections remains a persistent legal problem that threatens the fairness and legitimacy of democratic processes. A concrete example occurred during the 2024 General Election in Bandung Regency, where the Head of Majasetra Village was alleged to have engaged in politically biased actions. This study aims to analyze the legal framework and the implementation of the authority of the General Election Supervisory Agency (Bawaslu) in addressing violations of neutrality by village officials during elections. The research questions focus on: (1) how the law regulates Bawaslu’s authority and procedures in handling electoral crimes, and (2) how Bawaslu Bandung Regency implements that authority in the specific case. This research employs a normative juridical method with statutory, conceptual, and historical approaches, supported by empirical data from the field. The findings indicate that Bawaslu has a solid legal foundation through the Election Law Enforcement Center (Sentra Gakkumdu) for handling electoral violations. However, implementation at the regional level still encounters obstacles, such as limited human resources and weak inter-institutional coordination. Therefore, this study recommends strengthening the regulation of neutrality for village officials, enhancing Bawaslu’s institutional capacity, and ensuring consistent and firm law enforcement.